PENGARUH GOOGLE CLASSROOM BERBASIS WEB DENGAN IMPLEMENTASI MODEL PROJECT BASED LEARNING TERHADAP HASIL BELAJAR PESERTA DIDIK - Trisnawaty Junus Buhungo (Jurnal Pendidikan Fisika Undiksha, 2021)
This study aims to determine the learning outcomes of students in the use of the web-based Google Classroom application with the implementation of a project-based learning model in physics subject matter thermodynamics. In addition, students' responses to the treatments given were also considered as material for the evaluation of researchers. The research method applied is quantitative with a pre-experimental approach and using a one-shot case study as the research design. The place for implementation is carried out at Gorontalo 1 State Senior High School for the even semester of the 2019/2020 school year, with research subjects in class XI IPA 1, XI IPA 2, and XI IPA 8, with the number of students per class successively 30, 30, and 32. Hypostatic analysis of research data using the mean test technique with t test statistics, where hypothesis testing will be based on the KKM in the research school, namely 75. Based on the results of hypothesis testing, it is known that the t value for each class is 7.27, 3.44, and 4.17, which greater than the price of the t table which is 1.69 (thit> ttab), then the applicable statistical hypothesis is that H0 is accepted and Ha is rejected for all research classes, where H0 states that student learning outcomes are at least 75 with good predicate (B ).